Geometrical equivalence and action type geometrical equivalence of group representations - Simoes da Silva, J.; Tsurkov, A. (Algebra and Discrete Mathematics, 2020)
In this paper we construct an example of two representations (V₁,G₁) and (V₂,G₂) which are action type geometrically equivalent and groups G₁ and G₂ are geometrically equivalent, but the representations (V₁,G₁) and (V₂,G₂) are not geometrically equivalent.